2003
DOI: 10.1017/s136794300300338x
|View full text |Cite
|
Sign up to set email alerts
|

Translocation of an imperilled woodrat population: integrating spatial and habitat patterns

Abstract: Many species have strong habitat preferences that directly influence population viability. For successful reintroduction of threatened populations that rely on habitat structures, the correct placement of artificial structures is also important to population persistence. In this paper, we present a hierarchical approach to the problem of translocating animals that rely on permanent habitat structures, in which we first use population dynamics data to identify areas of suitable habitat, and then identify optima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 37 publications
(33 reference statements)
0
18
1
Order By: Relevance
“…Occupancy also showed a trend toward higher occupancy along abandoned roads (p=0.12). Contrary to some of the previous research (Olsen 1973;Balcom & Yahner 1996;Gerber et al 2003), no forest metrics were found to be relevant to either the presence or occupancy of a woodrat nest.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Occupancy also showed a trend toward higher occupancy along abandoned roads (p=0.12). Contrary to some of the previous research (Olsen 1973;Balcom & Yahner 1996;Gerber et al 2003), no forest metrics were found to be relevant to either the presence or occupancy of a woodrat nest.…”
Section: Discussioncontrasting
confidence: 99%
“…All artificial and natural nests were photographed, described, and mapped using a GPS unit (eTrex Venture® HC, Garmin™). Since woodrats are known to use multiple nests clustered within their territories (Linsdale & Tevis 1956;Gerber et al 2003), I conducted adaptive surveys to increase the probability of finding additional nests (Smith et al 2004). This involved walking in a spiral out from the nest I originally found up to a distance of 30 m away ( Figure 4).…”
Section: Nest Surveysmentioning
confidence: 99%
See 3 more Smart Citations